Geschlechterdifferenzierung in der Kindertageseinrichtung Eine qualitativ-rekonstruktive Studie - Kubandt, Melanie (Studien zu Differenz, Bildung und Kultur, 2016)
How should pedagogical staff in kindergartens deal with gender? Against the background of early pedagogical gender debates, this study offers an empirical insight into gender constructions of children, specialists and parents in the everyday life of a day care center. Furthermore, theoretical and empirical gaps in an early pedagogical debate about gender are shown, which arise if this is only conducted in front of the slide of gender justice with the aim of improving equal opportunities.